REVIEW ABOUT TEACHERS WHO TRANSFORM MULTIMODAL LEARNING ENVIRONMENTS: LANGUAGE TEACHING PROJECTS - Wanderley Marques Dantas, Jacqueline (Revista Gênero e Interdisciplinaridade, 2023)
The book “Teachers transforming multimodal learning environments: language teaching projects” clearly and didactically presents a new look at language teaching in Basic Education, proposing pedagogical strategies and creative activities based on multimodal learning environments with the help of digital technologies in the classroom context.